2019
DOI: 10.1097/hcr.0000000000000346
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Depressive Symptoms and Affect During Cardiac Rehabilitation

Abstract: Depressive symptom and affect improvements following CR were observed and most strongly associated with improvements in vitality and social support. Future research should explore how enhancement of these mechanisms may further improve depressive symptom and affect during CR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…For example, individuals may notice improvements in comfort or ability during exercise over the course of CR, and attribute this to better physical functioning. In addition, we recently reported that improvement in bodily pain was associated with improvement in depressed mood at the time of CR completion 23 ; improved bodily pain may encourage more physical activity and associated MET improvement. Conversely, individuals may be less apt to quickly recognize direct impacts of their ability to complete work or related tasks.…”
Section: Discussionmentioning
confidence: 96%
“…For example, individuals may notice improvements in comfort or ability during exercise over the course of CR, and attribute this to better physical functioning. In addition, we recently reported that improvement in bodily pain was associated with improvement in depressed mood at the time of CR completion 23 ; improved bodily pain may encourage more physical activity and associated MET improvement. Conversely, individuals may be less apt to quickly recognize direct impacts of their ability to complete work or related tasks.…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, some patients may start off high in negative mood and experiential avoidance, whereby CVPR engagement facilitates a reduction in these factors, contributing to eventual program completion. This perspective garners support from the CR literature, which shows that engagement in and support from exercise-based CR alleviates depression and anxiety symptoms (Zheng et al, 2019) and increases positive affect (Gathright et al, 2019). Future studies should examine whether EA changes throughout the entirety of CVPR programming, and how completion may be impacted.…”
Section: Discussionmentioning
confidence: 82%
“…3 Cardiac rehabilitation has proven to be beneficial for reducing hospitalizations, reinfarction, cardiac mortality, all-cause mortality, and improving daily function, depressive symptoms, and quality of life among patients with CVD. 1,[4][5][6][7][8][9][10][11][12][13] Traditional CR typically includes up to 36 1-hr, supervised, monitored exercise sessions over 12-18 wk. In August 2010, the CMS expanded coverage for CR to include intensive cardiac rehabilitation (ICR) programs, 14 based on demonstrated improvements in specific endpoints, including less progression of coronary heart disease, reduced need for coronary bypass surgery, and reduced need for percutaneous coronary interventions.…”
mentioning
confidence: 99%
“…Cardiac diagnoses that are approved by the Centers for Medicare & Medicaid Services (CMS) for referral to CR include myocardial infarction, coronary artery bypass surgery, stable angina pectoris, heart valve repair or replacement, coronary angioplasty or coronary stenting, heart transplant, and heart failure with reduced ejection fraction 3. Cardiac rehabilitation has proven to be beneficial for reducing hospitalizations, reinfarction, cardiac mortality, all-cause mortality, and improving daily function, depressive symptoms, and quality of life among patients with CVD 1,4–13…”
mentioning
confidence: 99%
See 1 more Smart Citation